Revealing the Silenced Spots: The Influence of Thomas and Znaniecki on the Study of Marginalized Aspects of Social Life - Kacperczyk, Anna (Qualitative Sociology Review, 2020)
This article aims to highlight the influence of the work of William I. Thomas and Florian Znaniecki on the perception of social reality by sociologists. I focus on the social practice of creating personal documents (memoirs, autobiographies, and letters) as a form of enacting individual agency and speaking their voice in the social space. I show the contribution of various social classes in this memorializing practice in Poland, reaching back to the 17th and 18th centuries. While doing so, I emphasize that a big part of society was practically muted in literary discourses. The voices of peasants and working-class were silenced as they had no access to the means which would enable them to speak and be represented in the discourse. Against this background, we can see how the “memoir competitions”—a very popular research practice being introduced in Poland by Znaniecki in 1921—have changed the power relations in the field of generating knowledge about social reality. The institution of Polish Memoirism that systematically gathered a huge number of autobiographies, enabled the poor and voiceless to speak and be heard by social researchers. In this sense, the monumental work of Thomas and Znaniecki was a trigger to the gradual process of revealing “blind spots” on the map of social reality and giving voice to the muted. Throughout the article, I return again and again to the main methodological questions, that is, what does it mean to include the consciousness of the participants of social life in sociological research, how to represent them in sociological theorizing, and how they can regain their voice in the scientific narrations about them.